2019
DOI: 10.18332/tid/105893
|View full text |Cite
|
Sign up to set email alerts
|

The association between cigarette smoking and obstructive sleep apnea

Abstract: INTRODUCTIONObstructive sleep apnea (OSA) is a serious sleep disorder characterized by repetitive episodes of paused or shallow breathing during sleep. Patients with OSA often have excessive daytime sleepiness. The role of cigarette smoking in OSA remains controversial. The aim of this study was to examine the relationship between cigarette smoking and OSA.METHODSIn this retrospective chart review, we reviewed 18-month sleep laboratory charts in central Taiwan. We collected data regarding sleep, current cigare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
23
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 33 publications
10
23
3
Order By: Relevance
“…Our results were consistent with the findings of the above studies. Like the studies of Hsu et al 7 and Casasola et al 8 , this study did not show an association between smoking history and the severity of OSA as represented by AHI; however, the ESS score of current/former smokers was slightly higher than in non-smokers. Daytime sleepiness is related to a variety of factors.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Our results were consistent with the findings of the above studies. Like the studies of Hsu et al 7 and Casasola et al 8 , this study did not show an association between smoking history and the severity of OSA as represented by AHI; however, the ESS score of current/former smokers was slightly higher than in non-smokers. Daytime sleepiness is related to a variety of factors.…”
Section: Discussionsupporting
confidence: 56%
“…The mucosa of the upper respiratory tract is easily affected by smoke. Long-term smoking causes edema, hyperplasia, hypertrophy, and ciliary dysfunction of mucosa of the upper airway 7,36 , leading to chronic inflammation of the upper airway, which in turn changes the biomechanical properties of the upper airway 37 , increasing its instability. In addition, nicotine damages the neuromuscular protective reflex 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study performed on over 5000 patients demonstrated that cigarette smoking correlates with a more severe form of obstructive sleep apnea and greater daytime sleepiness [58]. Similar results were obtained in a study by Hsu et al, where it was additionally found that smokers with OSA have a shorter total sleep time, reduced deep sleep and longer snoring period [59]. One should also note the synergic, adverse effect of obstructive sleep apnea and tobacco smoking on the circulatory system.…”
Section: Tobacco Smokingsupporting
confidence: 53%
“…Our results showed that a higher number of cigarettes smoked per day was significantly associated with higher daytime sleepiness, in agreement with previous studies 52,53 . While the association between cigarette smoking and OSA is plausible, the evidence is less than conclusive 54 . Cigarette smoking may worsen swelling and inflammation in the upper airway, affecting the neuromuscular function, and making snoring worse 55 .…”
Section: Multivariable Analysismentioning
confidence: 95%